2019
DOI: 10.1177/8756972819859746
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Design of the Project-Based Organization

Abstract: This article investigates organizational design choices and their antecedents for the design of project-based organizations. Extant literature acknowledges the diversity of project-based organizational forms, but neither the particular configurations of organizational design dimensions nor the reasons behind their differences are widely addressed. Based on interviews in 12 project-based organizations in various sectors, this study identifies three common organizational design configurations of project-based or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 73 publications
(155 reference statements)
1
34
0
1
Order By: Relevance
“…Its main business may be routine, but it is undertaking the project as an investment. Miterev & Turner (2017a,b) and Turner & Miterev (2019) identify several types of organization that use project management as a business process, to a different extent. With project-based organizations, almost all their work for customers is tailored or bespoke, and so project management is the business process they use, perforce.…”
Section: Projectificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Its main business may be routine, but it is undertaking the project as an investment. Miterev & Turner (2017a,b) and Turner & Miterev (2019) identify several types of organization that use project management as a business process, to a different extent. With project-based organizations, almost all their work for customers is tailored or bespoke, and so project management is the business process they use, perforce.…”
Section: Projectificationmentioning
confidence: 99%
“…Usually project-based organizations are project-oriented, but not always. Turner & Miterev (2019) interviewed a company that identified that it had three types of operation, which they labelled running, change and projects. Projects involved bespoke designs, and they used project management as the business process to manage that work.…”
Section: Projectificationmentioning
confidence: 99%
See 2 more Smart Citations
“…simple formulation, these holistic models are believed to be useful when used as analytical frameworks to study the ability of companies to adapt to novel environment. We have selected Galbraith's Star Model as a base for our analysis because it has evolved over time, incorporating elements from others models such as Waterman and Peter's or Nadler and Tushmans' [31], and because it has been selected in previous studies that have an analysis perspective on organizational design [11,[31][32][33]. Galbraith's organizational design is based on a five-factor schema (see Figure 1).…”
Section: Organizational Designmentioning
confidence: 99%